Depresi Sebagai Faktor Determinan Kualitas Hidup Lansia Yang Tinggal Di PSTW Di Masa Pandemi Covid-19 - Tomi Jepisa; Weni Mailita; Rischa Hamdanesti (Jurnal Ilmiah Kesehatan Mandira Cendikia, 2023)
The elderly group (elderly) is a group that is threatened with high morbidity and mortality in the Covid-19 pandemic. The Covid-19 pandemic is a challenge for the elderly as a vulnerable group and easily exposed to viruses. This pandemic condition has created various excessive fears and suspicions of other people and has resulted in depression, due to various kinds of obstacles and social restrictions, resulting in limited daily activities that have an impact on the quality of life for the elderly. This study aims to determine the relationship between the level of depression and the quality of life of the elderly during the Covid-19 pandemic at PSTW Kasih Sayang Ibu Batusangkar. This research used quantitative method with analytic descriptive design and cross sectional approach. The research sample is 68 elderly with purposive sampling technique. Data collection used a questionnaire which was carried out by visiting PSTW and data analysis techniques used the Chi Square test. That the level of depression is related to the quality of life of the elderly. Therefore, interventions are needed to increase interaction and sharing between the elderly to reduce depression and improve the quality of life of the elderly. There is a significant relationship between the level of depression on the quality of life of the elderly. The impact of the Covid-19 pandemic where the elderly who live in PSTW experience mild depression.